1998
DOI: 10.1021/np980338v
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Conversion of Vibsanin C to Vibsanin E and Structure of 3-Hydroxyvibsanin E from Viburnum awabuki

Abstract: Vibsanin E (4), a tricyclic vibsane-type diterpene, has been prepared in 50% yield from vibsanin C (2), a seven-membered ring vibsane-type diterpene by reaction with BF3.OEt2 at -78 degrees C. This chemical correlation not only established structure, including absolute configurations, but also has demonstrated a possible biosynthetic route to 4 via 2 derived from vibsanin B (1). The structure of 3-hydroxyvibsanin E (5), another example of a tricyclic seven-membered ring vibsane, isolated from the leaves of Vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…In the process of elucidating vibsane biochemical pathways Y. Fukuyama investigated the conversion of vibsanin C (2) to vibsanin E (3) [12] and found that conversion proceeded smoothly using borontrifluoride-diethyl ether, albeit in moderate yield (50 %) (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…In the process of elucidating vibsane biochemical pathways Y. Fukuyama investigated the conversion of vibsanin C (2) to vibsanin E (3) [12] and found that conversion proceeded smoothly using borontrifluoride-diethyl ether, albeit in moderate yield (50 %) (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Fukuyama et al found plausible biosynthetic pathways to two other vibsanin-type diterpenes from 2 and 3, respectively. When vibsanin B (2) was treated with BF 3 · Et 2 O in CH 2 Cl 2 under anhydrous conditions at À 788 for a short period, vibsanin E (5), a tricyclic vibsanin-type diterpene was obtained, in 50% yield [23]. They also reported a plausible biosynthetic pathway leading to cyclovibsanins from vibsanin C (3), as shown in Scheme 3 [21].…”
mentioning
confidence: 99%
“…In 1999 Fukuyama reported the isolation of 3-hydroxyvibsanin E ( 1 ) (Figure 1) from Viburnum awabuki 1 with an additional finding in Viburnum suspensum three years later 2. Across the entire spectrum of vibsane natural products α-hydroxylation is very rare,3,4 occuring only at position 3 of the bridged 7-membered ring class [e.g.…”
mentioning
confidence: 99%